Molecular Constants of the 2\(^1Π\) State of \(NaLi\) Molecule - Dung, Nguyen Tien; Trung, Le Canh; Khoa, Dinh Xuan; Bang, Nguyen Huy (Communications in Physics, 2013)
We report our determination of molecular constants for the 21Π state of NaLi from set of 732 spectral lines. Using the linear least-squares fitting method, an optimum set of molecular constants, which corresponds to dimensionless root mean of squares of deviation σ = 0.62 within 0.1 cm-1 experimental uncertainty, have been derived